2021
DOI: 10.4317/jced.57941
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the work of Spanish dentists: An early response to the pandemic

Abstract: Background This study aimed to assess the quality of the information about COVID-19 that Spanish dentists felt they were provided; their opinion about the actions by Health Institutions; their perception of the risk infection at work; and the security measures implemented to prevent contagion. Material and Methods A specific questionnaire was developed and made available online from March 18th to 20th 2020. Dentists working in Spain were invited to answer. Questions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
(26 reference statements)
2
14
0
1
Order By: Relevance
“…In May-June 2020, most participants perceived that looking after patients will pose an occupational risk of exposure to SARS-CoV-2 and agreed that the risk was not exaggerated, which is consistent with results obtained in other regions, 16 , 17 , 18 where a low level of comfort with infection control procedures has been reported, 15 as well as fear, anxiety and depression. 14 , 16 , 19 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In May-June 2020, most participants perceived that looking after patients will pose an occupational risk of exposure to SARS-CoV-2 and agreed that the risk was not exaggerated, which is consistent with results obtained in other regions, 16 , 17 , 18 where a low level of comfort with infection control procedures has been reported, 15 as well as fear, anxiety and depression. 14 , 16 , 19 …”
Section: Discussionsupporting
confidence: 82%
“… 19 However, early in the pandemic gaps were observed between the perceived occupational risk and the implementation of enhanced infection control procedures. 14 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Since the WHO declared the COVID-19 outbreak a pandemic in March 2020 [ 38 ], numerous dental practice modifications have been gradually implemented to adhere to international biosafety protocols and reduce the risk of infection [ 39 , 40 ]. In this sense, it is evident that measures adopted, such as hand hygiene, the use of masks, the suspension of activities with a high concentration of people, and social distancing, have triggered fear, anxiety, stress, and uncertainty mainly in health-care professionals, including dentists [ 10 , 11 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, dental practice has undergone numerous changes during the pandemic, specifically considering lockdowns and isolation measures. Studies conducted globally involving dental staff show that this situation has had a significant impact on their personal life, financial status, and the prospects of their professional career [ 9 , 10 , 11 , 12 ]. Similarly, other effects of the pandemic including the field of nutrition (a possible increase of overweight and obesity) [ 13 ], changes in family dynamics by the presence of children, or elders that represent some burden when they are economic providers, household income, among others [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The measures incorporated in dental practices for their adaptation, according to this study, have not required large investments in HEPA filter suction systems (5.3%), nor in other air purification systems (7.8%), which evacuate the air from an area by dissipating the atmosphere. The vacuum system type may influence the risk of aerosol transmission of SARS-Cov-2 [40], but it should be considered as a complementary infection control measure considering the functionality and limitations of HEPA filter systems [41]. Recent studies have confirmed that if there is no availability for mechanical ventilation, natural ventilation may not be recommended during activities of competence, such as ultrasonic scaling or when using airborne spreading devices, which under standard conditions seem to release high levels of particulate matter that can act as vectors of infectious agents and contaminate patients and dental practitioners [42].…”
Section: Discussionmentioning
confidence: 99%